Simulasi variasi sudut lidah volute casing terhadap kecepatan aliran udara pada blower tipe forward blade - Husna Endry Syafa‘at; Ipung Kurniawan; Radhi Ariawan; Agus Santoso (P3M Politeknik Negeri Cilacap, 2025)
Optimization of volute design is essential for the performance of centrifugal pumps and blowers. This study investigates the effect of volute tongue angle variation on air velocity and flow rate in volute casing design using flow simulations. The volute design was tested with tongue angles of 15°, 30°, 45°, 60°, and 75°, based on theoretical equations of flow rate and volute radius. Simulation results indicated that increasing the volute tongue angle enlarges the volute cross-sectional area. Generally, this enlargement decreases air velocity but increases the flow rate. A 75° tongue angle produced the highest flow rate of 4.860 m³/s, while the highest velocity, 21.35 m/s, was observed at 15°. This behavior aligns with the principle of mass conservation, where a larger cross-sectional area leads to reduced fluid velocity. These findings suggest that volute designs with larger tongue angles can optimize the flow capacity.